Well-camouflaged Skin Graft Donor Sites in the Hand. Issue 4 (December 2015) - Tan, Ruth E.; Ying, Camelia Tang Qian; Sean, Lai Wei Hong; Lee, Ellen Y.; Foo, Tun-Lin
Abstract : Three full-thickness skin graft sites within the hand where the donor sites are well blended with surrounding skin contour and crease are described. Two of these donor sites are located within the digit and these provide nonglaborous skin for small defects of the hand, whereas the third donor site along the palmar crease provides glaborous skin. These donor sites provide ease of access, minimal morbidity, and well-matched skin for resurfacing of small defects around the hand. The indications, contraindications, and technical points of each donor site are discussed.